1979
DOI: 10.1021/jm00194a023
|View full text |Cite
|
Sign up to set email alerts
|

Antimycotic imidazoles. Part 4. Synthesis and antifungal activity of ketoconazole, a new potent orally active broad-spectrum antifungal agent

Abstract: The preparation and antifungal properties of cis-1-acetyl-4-[4-[[2-(2,4-dichlorophenyl)-2-(1H-imidazol-1-yl-methyl)-1,3-dioxolan-4-yl]methoxy]phenyl]piperazine (I) are described. Ketoconazole has, at low oral doses, a high in vivi activity against vaginal candidosis in rats and against cutaneous candidosis in guinea pigs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
123
0
2

Year Published

1988
1988
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 329 publications
(131 citation statements)
references
References 2 publications
0
123
0
2
Order By: Relevance
“…Ketoconazole is an orally active, antifungal imidazole derivative synthesized and developed by Janssen Pharmaceutica in 1977 (127,302). It is considered to be the "gold standard" among the azole derivative antifungal drugs.…”
Section: Ketoconazolementioning
confidence: 99%
“…Ketoconazole is an orally active, antifungal imidazole derivative synthesized and developed by Janssen Pharmaceutica in 1977 (127,302). It is considered to be the "gold standard" among the azole derivative antifungal drugs.…”
Section: Ketoconazolementioning
confidence: 99%
“…6,7 In other studies, ketoconazole showed a wide spectrum of antimycotic activity against dermatophytes, Malassezia species and Candida species in vitro. 10 Topical ketoconazole 2% cream was used in this study for the treatment of Pityriasis versicolor, which had previously given 80%-90% of cure rate in the treatment of Pityriasis versicolor in other studies.…”
Section: Time Periodmentioning
confidence: 99%
“…Each of the reconstituted extract was added into 100 ml of respective medium in a conical flask, stirred and let to stand at 40-50 o C for 30 min. The positive control consisted of ketoconazole (Keto) incorporated at 10µg/ml of media (Heeres et al, 1979).The medium in each flask was poured in four petri dishes (replicates).…”
Section: Extractionmentioning
confidence: 99%